2021
DOI: 10.3390/ijms22084029
|View full text |Cite
|
Sign up to set email alerts
|

CgEnd3 Regulates Endocytosis, Appressorium Formation, and Virulence in the Poplar Anthracnose Fungus Colletotrichum gloeosporioides

Abstract: The hemibiotrophic ascomycete fungus Colletotrichum gloeosporioides is the causal agent of anthracnose on numerous plants, and it causes considerable economic losses worldwide. Endocytosis is an essential cellular process in eukaryotic cells, but its roles in C. gloeosporioides remain unknown. In our study, we identified an endocytosis-related protein, CgEnd3, and knocked it out via polyethylene glycol (PEG)-mediated protoplast transformation. The lack of CgEnd3 resulted in severe defects in endocytosis. C. gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 96 publications
1
9
0
Order By: Relevance
“…In the Δ CgMsb2Sho1 double mutant, very few appressoria formed, and those that did form showed defects in both appressorium penetration and invasive growth (Figure 2a–d ). Reactive oxygen species ( ROS) play an essential role in plant defence responses, and we previously revealed that the small G protein CgCdc42 and the endocytosis‐related protein CgEnd3 are also required for invasive growth, while exogenous treatment with the ROS inhibitor diphenyleneiodonium chloride (DPI) restored the defect efficiently (Wang et al, 2021a ; Wang et al, 2018 ). Therefore, DPI was added during conidial germination at a final concentration of 5 µM.…”
Section: Resultsmentioning
confidence: 99%
“…In the Δ CgMsb2Sho1 double mutant, very few appressoria formed, and those that did form showed defects in both appressorium penetration and invasive growth (Figure 2a–d ). Reactive oxygen species ( ROS) play an essential role in plant defence responses, and we previously revealed that the small G protein CgCdc42 and the endocytosis‐related protein CgEnd3 are also required for invasive growth, while exogenous treatment with the ROS inhibitor diphenyleneiodonium chloride (DPI) restored the defect efficiently (Wang et al, 2021a ; Wang et al, 2018 ). Therefore, DPI was added during conidial germination at a final concentration of 5 µM.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated the change in the cell wall composition of Δ CgnoxB , Δ CgnoxR , and Δ CgnoxAnoxB . Chitin synthases participate in the biosynthesis of chitin and are involved in the cell wall integrity of filamentous fungi ( Yang and Zhang, 2019 ; Wang et al., 2021 ). Therefore, the expression changes of chitin synthases in the mutants were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the expression changes of chitin synthases in the mutants were investigated. There were seven chitin synthases ( CgCHS ) identified in C. gloeosporioides ( Wang et al., 2021 ). The qRT-PCR assay ( Figure 8C ) showed that in Δ CgnoxA , the relative expression levels of CgCHS2 , CgCHS3 , CgCHS4 , CgCHS6 , and CgCHS7 increased over twofold; meanwhile, all seven genes were upregulated in Δ CgnoxB .…”
Section: Resultsmentioning
confidence: 99%
“…Appressorium development is essential to penetrate the host. To explore the underlying mode of action of CPF’s effect on appressorium formation, we tested four genes reported to participate in the regulation of appressorium formation in Colletotrichum species ( Miyara et al, 2010 ; Lin et al, 2012 ; Dubey et al, 2016 ; Wang et al, 2021 ). The expression of these appressorium formation-related genes was significantly suppressed by CPF treatment ( Figure 7H ).…”
Section: Discussionmentioning
confidence: 99%